The Influence of The Ok Oce Program on Development of Business Entrepreneurs and Growth of Employment in South Jakarta in 2017 – 2018 - Putra, Amin Khasyim Azuz (Universitas Mercu Buana, 2020)
The purpose of this study is to examine the influence of the development of entrepreneurs and job growth. The population of this study is a entrepreneurs from various background who join Program OK OCE as a new entrepreneurs. those data analyze by using simple regression equation from data statistic. The result is showen that in partial connection from Program OK OCE to the development of entrepreneurs is positive and significant 14 % with correlation between those are weak 0.377, partial connection from Program OK OCE to job growth the result is positive and significant 57% with correlation between those variabel are strong 0.758.